The attitudes of communicators toward cybersecurity concerning security, safety in national institutions - Murad, Husain A.; Qudah, Mohammad (Frontiers in Communication, 2025)
This study aimed to assess the attitudes of communicators towards cybersecurity in relation to national security and safety standards in Kuwait. The study examined key factors influencing communicators’ use of cybersecurity technologies. It also analyzed the legislation regulating this field. Additionally, it explored how these laws are used to shape media and public messages that promote national security and safety. To achieve this, the study followed a quantitative descriptive approach, using a questionnaire as the primary tool. The questionnaire was distributed to a sample of 140 communicators in Kuwaiti national institutions. The study found that Kuwaiti national institutions have laws and legislation related to cybersecurity. These regulations are linked to cybersecurity management and are continuously updated to meet digital and media transformation needs. The results also highlighted the presence of laws designed to curb spam messages. Also, a computer emergency response team is in place. However, communicators use different approaches to tackle cybersecurity threats, leading to a noticeable disparity in their methods. The study identified several key methods for raising cybersecurity awareness. One approach was using social media to educate the public. Another involved organizing lectures and seminars on cybersecurity. Additionally, meetings with specialists were held to increase awareness among school students. Furthermore, to strengthen cybersecurity readiness in national institutions, the study offers several actionable recommendations. These include integrating communicators into cybersecurity decision-making processes, enhancing training programs tailored to their roles, and fostering stronger collaboration between technical experts and communicators to ensure effective information dissemination. Moreover, national institutions should prioritize cybersecurity awareness campaigns, incorporate communicators in incident response planning, and adopt structured policies that align legislative frameworks with practical enforcement strategies. These measures will not only improve institutional cybersecurity resilience but also empower communicators to play a proactive role in mitigating cyber threats. In addition, this study recommends participating in knowledge exchange platforms, attending conferences, and enhancing awareness of media messages to benefit from collective experience and share best practices. It also suggests giving communicators priority in media measures, such as responding to threats or engaging with stakeholders. Hence, communication and media strategies in the field of cybersecurity should be integrated and activated more effectively across different media platforms.